Pengembangan Model Sistem E-Library Studi Kasus AMIK HASS - Darsiti .; Budiman . (SisInfo, 2020)
AMIK HASS Bandung is a private college that has an Informatics Management study program. AMIK HASS Bandung is divided into several parts of the work, one of which is the library section. The process of borrowing and searching books in this library is still done by recording and searching on the documents that have been provided so that the process of borrowing and searching books takes less time than the need for an application that helps the loan process and search books more effectively and the results of reports are quick, precise and accurate. In this study, the analysis and design of the system used the approach of object models namely Use Case Diagram, Activity Diagram, Sequence Diagram, and Class Diagram. In addition, the authors also used data collection techniques in the form of observations, interviews, and library studies related to this research and the software used is PHP and MySQL. Development results can assist the library in managing transaction data in the library.